2012
DOI: 10.1186/1746-6148-8-167
|View full text |Cite
|
Sign up to set email alerts
|

BLV-CoCoMo-qPCR: a useful tool for evaluating bovine leukemia virus infection status

Abstract: BackgroundBovine leukemia virus (BLV) is associated with enzootic bovine leukosis, which is the most common neoplastic disease of cattle. BLV infects cattle worldwide, imposing a severe economic impact on the dairy cattle industry. Recently, we developed a new quantitative real-time polymerase chain reaction (PCR) method using Coordination of Common Motifs (CoCoMo) primers to measure the proviral load of known and novel BLV variants in BLV-infected animals. Indeed, the assay was highly effective in detecting B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
64
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 30 publications
7
64
0
5
Order By: Relevance
“…Second, the present results clearly indicate that the sensitivity of BLV-CoCoMo-qPCR-2 was higher than that of nested PCR because we found a number of cattle on Leyte, Iloilo and Luzon Islands that were BLVpositive as determined by the BLV-CoCoMo-qPCR-2 but were negative for BLV provirus as determined by nested PCR. This result showed the same tendency as discussed in our previous publications [7,12], showing that our original BLV-CoCoMo-qPCR is highly specific and sensitive and able to detect BLV in samples that are negative by the nested PCR assay. In addition, our previous paper [7] demonstrated that the positive rate for the nested PCR in cattle correlated with the proviral load determined by the original BLV-CoCoMo-qPCR as follows: 1) positive rates for the nested PCR ranged from 62.9 % to 98.5 % among animals with proviral copy numbers ranging from 10 0 to 10 4 copies per 10 5 cells, and 2) the positive rate for nested PCR was 100 % in cattle with high proviral loads ([10 4 copies per 10 5 cells).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Second, the present results clearly indicate that the sensitivity of BLV-CoCoMo-qPCR-2 was higher than that of nested PCR because we found a number of cattle on Leyte, Iloilo and Luzon Islands that were BLVpositive as determined by the BLV-CoCoMo-qPCR-2 but were negative for BLV provirus as determined by nested PCR. This result showed the same tendency as discussed in our previous publications [7,12], showing that our original BLV-CoCoMo-qPCR is highly specific and sensitive and able to detect BLV in samples that are negative by the nested PCR assay. In addition, our previous paper [7] demonstrated that the positive rate for the nested PCR in cattle correlated with the proviral load determined by the original BLV-CoCoMo-qPCR as follows: 1) positive rates for the nested PCR ranged from 62.9 % to 98.5 % among animals with proviral copy numbers ranging from 10 0 to 10 4 copies per 10 5 cells, and 2) the positive rate for nested PCR was 100 % in cattle with high proviral loads ([10 4 copies per 10 5 cells).…”
Section: Discussionsupporting
confidence: 88%
“…This result showed the same tendency as discussed in our previous publications [7,12], showing that our original BLV-CoCoMo-qPCR is highly specific and sensitive and able to detect BLV in samples that are negative by the nested PCR assay. In addition, our previous paper [7] demonstrated that the positive rate for the nested PCR in cattle correlated with the proviral load determined by the original BLV-CoCoMo-qPCR as follows: 1) positive rates for the nested PCR ranged from 62.9 % to 98.5 % among animals with proviral copy numbers ranging from 10 0 to 10 4 copies per 10 5 cells, and 2) the positive rate for nested PCR was 100 % in cattle with high proviral loads ([10 4 copies per 10 5 cells). Therefore, cattle that were BLVpositive as determined by the BLV-CoCoMo-qPCR-2 but were negative for BLV provirus as determined by nested PCR may have a very low copy number of BLV, which cannot be detected by nested PCR.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…BLV-infected cows produce less milk, with industry losses in the US dairy industry estimated at $525 million per year [14]. BLV infection in cattle is usually identified using serological methods such as enzyme-linked immunosorbent assay (ELISA), Passive hemagglutination test (PHA), or agar-gel immunodiffusion tests (AGID) [7]. However, these tests cannot allow judgments as to the degree of BLV-induced disease progression [7].…”
mentioning
confidence: 99%